Densification, microstructures, and mechanical properties of (Zr, Ti)(C, N) ceramics fabricated by spark plasma sintering. Issue 14 (November 2022) - Liang, Lanqing; Wei, Boxin; Wang, Dong; Fang, Wenbin; Chen, Lei; Wang, Yujin
Abstract: Dense (Zr, Ti) (C, N) ceramics were fabricated by spark plasma sintering (SPS) at 1900–2000 °C using ZrC, TiCN and ZrH2 powders as raw materials. A single Zr-rich (Zr, Ti)(C, N) solid solution was formed in Zr0.95 Ti0.05 C0.975 N0.025 and Zr0.80 Ti0.20 C0.90 N0.10 ceramics (nominal composition). A Ti-rich solid solution appears in Zr0.50 Ti0.50 C0.75 N0.25 ceramics. The coaddition of TiCN and ZrH2 promoted the densification of (Zr, Ti) (C, N) ceramics by forming solid solutions and carbon vacancies, which could reduce critical resolved shear stress (CRSS) and promote carbon and metal atom diffusion. ZrC-45 mol% TiCN-10 mol% ZrH2 (raw powder composition) possesses good comprehensive mechanical properties (Vickers hardness of 24.5 ± 0.9 GPa, flexural strength of 503 ± 51 MPa, and fracture toughness of 4.3 ± 0.2 MPa·m 1/2 ), which reach or exceed most ZrC-based (Zr, Ti) C and (Zr, Ti) (C, N) ceramics in previous reports. Highlights: The coaddition of TiCN and ZrH2 promoted the densification of ceramics by forming solid solutions and carbon vacancies. The densification mechanism changes from grain boundary sliding to grain boundary diffusion at 1900-2000 ℃ via SPS. The mechanical properties of Z50T10H exceed most ZrC-based (Zr, Ti) C and (Zr, Ti) (C, N) ceramics in previous reports.